Sistem Pendukung Keputusan Rekomendasi Emiten Saham Menggunakan Metode Simple Additive Weighting - Renny Puspita Sari; Muhamad Rabil Maulana (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
In the current era, stock investing is an instrument that is currently popular with Indonesian youth, stock investing is one of the many investment options that are increasingly in demand by various groups. Investing in stocks is an activity to refrain from enjoying the present for more enjoyment in the future, this investment often brings someone to be wiser in managing their finances, choosing good stocks is not an easy thing for some investors it takes many factors and ratios - financial ratios to choose stocks that can provide financing by the initial investment objectives. Therefore we need a system to help these problems. The system is a decision support system that can assist in making decisions from the available options. This Stock Issuer Recommendation Decision Support System Using the Simple Additive Weighting Method is here to assist decision-makers to choose good issuers or stocks to collect so that they can provide good profits in the future. The results of the calculation on the system using the Simple Additive Weighting method will show the best suitable stock recommendations for the user based on the data they enter.